Penerapan Konseling Lintas Budaya dan Studi Feminis Poskolonial Terhadap Penindasan Budaya Patriarki - Loppies, Paula Alfa; de Haan, Arly Elisabeth Maria (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
The purpose of this research is to know the context of oppression in patriarchal culture of the women of Timor, know the efforts made by the women of East Timor for overcoming the cultural oppression of patriarchy, and designed the cross cultural Counseling efforts (Cross-culture counseling) in bridging the different understanding between women of Timor (ex-migrant workers) and the local community. To achieve that goal then the research method used is the method of qualitative phenomenological studies that are descriptive- analysis. Results of the study stated that the issue of the oppression of women in a patriarchal society culture, particularly in the village of Tetaf still continue to occur. This is also the reason for some women to get out of the village of Tetaf and became migrant workers woman. Experience being Labor Lady gives a change of perception for women of Timor, but it is not able to change their position as 'the second' when they returned to the village of Tetaf. Patriarchal culture remained the colonizer for them, since their return to Tetaf, their opinions remain dominated by men, even their dreams to use the money to improve the lives of being dispersed. Cross cultural counseling model that can be offered are: Counselor, client, with the introduction of observation culture (positive to negative values), brings together the values in line, and provides a workaround option.